2013
DOI: 10.1002/pssa.201370056
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous iodide - a p-type transparent semiconductor: history and novel applications (Phys. Status Solidi A 9∕2013)

Abstract: Cuprous iodide has been investigated since 1907 when Karl Bädeker prepared this material from metallic copper thin films with subsequent iodization and reported it as fully transparent conductor. Nowadays CuI is recognized as p‐type wide bandgap, transparent semiconductor, offering rather high hole mobilities of so far up to 10 Vs∕cm2 in thin films. The charge carrier density is primarily controlled via the amount of copper vacancies. CuI has been prepared as bulk material and substrate and thin film as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
97
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 0 publications
12
97
0
10
Order By: Relevance
“…[62] It is also noteworthy to acknowledge copper iodide (CuI) as it is a well-known p-type metal halide also based on Cu(I) and has been employed in several device applications as a hole-transporting layer. [63][64][65][66] Although the conductivity of γ-CuI is electronic, α-CuI and β-CuI also show strong ionic conductivity [67] and may present a challenge in the development of electronic devices. However, a full discussion on CuI is beyond the scope of this work as it is a common metal halide and does not possess the quasi-molecular nature as in the case of pseudohalides.…”
Section: Related Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[62] It is also noteworthy to acknowledge copper iodide (CuI) as it is a well-known p-type metal halide also based on Cu(I) and has been employed in several device applications as a hole-transporting layer. [63][64][65][66] Although the conductivity of γ-CuI is electronic, α-CuI and β-CuI also show strong ionic conductivity [67] and may present a challenge in the development of electronic devices. However, a full discussion on CuI is beyond the scope of this work as it is a common metal halide and does not possess the quasi-molecular nature as in the case of pseudohalides.…”
Section: Related Materialsmentioning
confidence: 99%
“…However, a full discussion on CuI is beyond the scope of this work as it is a common metal halide and does not possess the quasi-molecular nature as in the case of pseudohalides. To this end, Grundmann et al [67] have recently published a comprehensive review of the properties and applications of CuI.…”
Section: Related Materialsmentioning
confidence: 99%
“…13 In an effort to address some/all of these issues, a range of alternative HTL materials have been investigated, including PSS-free vapor phase polymerized PEDOT, 14,15 graphene oxide, 16 22 It exhibits three crystalline phases, namely, a, b, and c, 23 of which the c-CuI zinc blende structure (cubic), known to form at deposition temperatures below 390 C, is the most interesting for our purpose. c-CuI is a ptype, wide-bandgap ($3.1 eV) 24 semiconductor and, due to its optical transparency and favourable Fermi level energy, has previously been used as a HTL in solid-state dye-sensitized solar cells. 25 CuI has also been incorporated in organic light emitting diodes (OLEDs) 26 and organic solar cells.…”
mentioning
confidence: 99%
“…Furthermore, XRD analysis revealed that both samples exhibit exclusively (111) and (222) peaks, consistent with a dominant c-CuI zinc blende structure. 24 CuI(eva) films appear, however, to be composed of larger crystallites than CuI(sln) layers (Table S1). 31 Again, this difference may be responsible for the stoichiometric, and hence electronic, differences between the two types of CuI layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation